It is mainly about where you work!: Labor demand in the Colombian manufacturing sector - Luis Eduardo Arango Thomas; Francesca Castellani; Nataly Obando (Inter-American Development Bank (IDB), 2016)
Using the Colombian Annual Manufacturing Survey (EAM) between 2000 and 2013, this paper investigates the existence of heterogeneity in the labor demand within the industrial sector. Long run own-price, output and TFP elasticities vary across a variety of dimensions such as regions, sectors and plant sizes depending on workers' skills and contract modalities (open-ended or temporary). Hence, it matters where one works. Such disparities should be taken into account in the design of policies that promote labor market performance, as outcomes, beyond intentions, are unlikely to be homogenous.
Keywords: J23; R32; 330; labor demand; skilled workers; unskilled workers; regional disparities; sector disparities